Paraneoplastic Dermatomyositis with Carcinoma Cervix: A Rare Clinical Association. (17th December 2014) - Kumar, Sumir; Mahajan, B. B.; Kaur, Sandeep; Singh, Amarbir
Abstract : Dermatomyositis is an uncommon inflammatory myopathy associated with cutaneous manifestations. It may also occur as paraneoplastic syndrome associated with various malignancies, most common of which being lung, breast, stomach, rectum, kidney, or testicular cancer. A postmenopausal woman presented to us with generalized itching along with skin rash and proximal muscle weakness of 2 years' duration. Examination revealed heliotrope rash and mechanic hands and muscle power 2/5 in proximal muscle groups of both upper and lower limbs. A clinical diagnosis of dermatomyositis was made which was supported by raised lactate dehydrogenase levels and skin biopsy findings. Past history was significant for vaginal discharge and bleeding per vagina. Further work-up revealed carcinoma cervix and she was referred to oncology department for further management. Temporal relationship and improvement of muscle weakness with treatment of underlying neoplasm supported its paraneoplastic nature. So, final diagnosis of keratinizing squamous cell carcinoma of cervix with paraneoplastic dermatomyositis was made. A nationwide cohort study of 1, 012 patients with dermatomyositis in Taiwan revealed only 3 patients with cervical cancer. So this case is being reported for its rare association with carcinoma cervix and to highlight the need of detailed evaluation for underlying malignancies in patients with dermatomyositis.